Culture Wars : (Cambridge University Press, 2003)
Twelve essays from a team of European experts examine the struggle that broke out between secular and religious forces in late nineteenth-century Europe. They highlight the role of trans-national forces and their interaction with local conditions. This collection combines an account of the impact of secular-religious strife, at the level of high politics, with case studies that elucidate the meaning of culture war for specific regions and communities.